2020
DOI: 10.1155/2020/8884304
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Stakeholder Perspective on Safety Risk Factors of Metro Construction: A Social Network Analysis

Abstract: The rapid development of the metro has greatly relieved the traffic pressure on the urban ground system, but the frequency of metro construction accidents is also increasing year by year. Due to the complex construction process of the metro, once an accident occurs, casualties and property damage are extremely serious. The safety risk factors triggered by different stakeholders were the primary cause of accidents during the metro construction phase. This paper builts a social analysis network of safety risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…(2018) identified four connection modes between risk management and stakeholder management, which confirmed the effectiveness of integrated management of the two. Based on the network of safety risk factors in metro construction, Lu et al. (2020) identified key safety risk factors and proposed risk control strategies from the perspective of stakeholders.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2018) identified four connection modes between risk management and stakeholder management, which confirmed the effectiveness of integrated management of the two. Based on the network of safety risk factors in metro construction, Lu et al. (2020) identified key safety risk factors and proposed risk control strategies from the perspective of stakeholders.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies have also validated the pivotal role of government supervision in improving safety performance, including metro construction safety (Lu and Zhang, 2010), coal mine safety (Chen et al. , 2016) and urban public transportation (Xue et al.…”
Section: Previous Researchmentioning
confidence: 99%
“…Recent research has also widely validated the pivotal role of government supervision in improving workplace safety. Based on the analysis of 42 accident cases, Lu and Zhang found that unfavorable government supervision is one of the critical safety risk factors during the metro construction phase [ 41 ]. Besides, in coal mine industry, Chen et al revealed that the establishment of safety supervision institutions could noticeably reduce the industry’s death rate [ 42 ].…”
Section: Literature Reviewmentioning
confidence: 99%